Differential profiles of cognitive and behavioral inflexibility in addictive disorders - Lim, Tsen Vei; Ersche, Karen (Current Opinion in Behavioral Sciences, 2024)
Patients with addictive disorders (encompassing substance and behavioral addictions) often behave in ways that have been described as rigid and inflexible. This behavioral profile has been proposed to be explained by impairments in cognitive and behavioral flexibility that are shared by all addictive disorders. To evaluate this assertion, we reviewed the literature to determine similarities and differences in the performance of patients with either substance-related or behavioral addictions on well-established paradigms of cognitive and behavioral flexibility. Contrary to the widely-held view, we found that different addictive disorders have contrasting profiles of cognitive and behavioral inflexibility, suggesting that inflexible behavior - though conceptually similar in all addictive disorders - appears to be underpinned by different neuropsychological processes.